Effect of antioxidants during bovine in vitro fertilization procedures on spermatozoa and embryo development - Gonçalves, Fernanda da Silva [UNESP]; Barreto, Letícia Siqueira de Sá [UNESP]; Arruda, Rubens Paes de; Perri, Silvia Helena Venturoli [UNESP]; Mingoti, Gisele Zoccal [UNESP] (Blackwell Verlag, 2010)
Increased amounts of reactive oxygen species (ROS) duringin vitro fertilization (IVF) may cause cytotoxic damage togametes, whereas small amounts of ROS favour spermcapacitation. The aim of this study was to investigate theeﬀect of antioxidants [50 lM b-mercaptoethanol (b-ME) and50 lM cysteamine (Cyst)] or a pro-oxidant (5 mM buthioninesulfoximine) on the quality and penetrability of spermatozoainto bovine oocytes and on the subsequent embryo develop-ment and quality when added during IVF. Sperm quality,evaluated by the integrity of plasma and acrosomal mem-branes, and mitochondrial function, was diminished (p < 0.05) after 4-h culture in the presence of antioxidants.Oocyte penetration rates were similar between treatments (p > 0.05), but antioxidants adversely aﬀected the normalpronuclear formation rates (p < 0.05). The incidence ofpolyspermy was high for b-ME (p < 0.05). No diﬀerenceswere observed in cleavage rates between treatments (p > 0.05). However, the developmental rate to the blasto-cyst stage was adversely aﬀected by Cyst treatment (p < 0.05). The quality of embryos that reached the blasto-cyst stage, evaluated by total, inner cell mass (ICM) andtrophectoderm cell numbers and ICM/total cell ratio wasunaﬀected (p > 0.05) by treatments. The results indicate that ROS play a role in the fertilizing capacity in bovinespermatozoa, as well as in the interaction between thespermatozoa and the oocytes. It can be concluded thatsupplementation with antioxidants during IVF proceduresimpairs sperm quality, normal pronuclear formation andembryo development to the blastocyst stage.